Innovation and Business Model: a case study about integration of Innovation Funnel and Business Model Canvas - Zandoval Bonazzi, Fábio Luiz; Ari Zilber, Moisés (Review of Business Management, 2014)
Unlike the past, currently, thinking about innovation refers to a reflection of value cocreation through strategic alliances, customer approach and adoption of different business models. Thus, this study analyzed and described the innovation process of company DSM, connecting it to concepts of organizational development strategies and the theory of business model. This is a basic interpretive qualitative research, developed by means of a single case study conducted through interviews and documentary analysis. This study enabled us to categorize the company business model as an open, unbundled and innovative model, which makes innovation a dependent variable of this internal configuration of value creation and value capture. As a theoretical contribution, we highlight the convergence and complementarity of the “Business Model Canvas” tool and “Innovation Funnel,” used here, to analyze the empirical case.